Analisis Strategi Pengembangan Usaha Keripik Pisang Dalam Meningkatkan Kesejahteraan Masyarakat Di Kelurahan Yosodadi Kecamatan Metro Timur - Ramadhan, Ari Taliq; Japlani, Ardiansyah (Jurnal Manajemen DIVERSIFIKASI, 2022)
Ari Taliq Ramadhan. 2022. Analysis of Banana Chips Business Development Strategy in Improving Community Welfare in Yosodadi Village.Essay. Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro. Supervisor (1) Ardiansyah Japlani, SE, MBA. (2) Fitriani, SE, MM Keywords : Development Strategy, Quantitative,IFE,EFE With the Covid-19 pandemic, the sales of chips have decreased shows data on sales of banana chips in the village of Yosodadi in 2016, 2017, 2018, 2018, 2019 experienced an increase and in 2020 it decreased With a decrease selling banana chips has an impact on the welfare of the community This research was conducted using a quantitative descriptive research method because it aims to to describe the state of phenomena in the field. (sugiyono:35) research method Quantitative research is a research method based on the philosophy of positivism, used to researching on certain populations and samples, collecting data using instruments research, date analysis is quantitative/statistical, with the aim of testing the hypothesis that has been established The current business condition of bud chips is based on internal and external factors that The internal environment of the Tunas Chips company has strength in the capital that has been fulfilled Based on the IFE and EFE matrices, the company is in a position in quadrant I with the strategy that can be chosen is Grow and Built where the suitable strategy is Market Development strategy, Product Development strategy and Market Penetration Strategy Preferably, companies develop product marketing that can reach in various areas not only within the Metro City but throughout the city in Lampung Province It is better for entrepreneurs to make production cost efficiency in order to reduce the cost of producing banana chips